A NEW POTTERY MANUFACTURING CENTER AT NOVAE - Dyczek, Piotr (Rei Cretariae Romanae Fautorum Acta, 2024)
The site of Novae in northern Bulgaria is known foremost as a fortress of the First Italic Legion. Its history after the Gothic raids of the mid 3rd century AD is not as well known, simply because it has become recently the object of investigation carried out by the Center for Archaeological Research of Warsaw University. A change in the architecture inside the old castrum occurs at about this time. The aban- doned legionary buildings, such as the army hospital, were then replaced by civilian architecture, and a section of the fortifications was added on the east. Alterations can be observed also in the immediate vicinity of the old fortress.